The Influence of Budget Planning and Human Resource Competence on the Effectiveness of Financial Management at the Dumbo Raya Sub-District Office of Gorontalo City - Febriandi B. Hama; Mattoasi; Amir Lukum (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to examine and analyze the influence of budget planning and human resource competence on the effectiveness of financial management at the Dumbo Raya District Office, Gorontalo City. The approach used in this research is a quantitative approach with a causal associative method. Data were collected by distributing questionnaires to 46 respondents determined using the saturated sampling (census) technique. Data analysis techniques include classical assumption tests, multiple linear regression analysis, and hypothesis testing (t-test and F-test) with the assistance of SPSS 26 software. The results of the study indicate that: (1) Budget planning has a positive and significant effect on the effectiveness of financial management with a moderate category of influence. (2) Human resource competence has a positive and significant effect on the effectiveness of financial management with a small category of influence. (3) Simultaneously, budget planning and human resource competence have a significant effect on the effectiveness of financial management with a strong category of influence. The coefficient of determination (Adjusted R Square) indicates that these two independent variables are able to explain the variation in financial management effectiveness by 69.9%, while the remaining 30.1% is explained by other factors outside of this research model.